Perceptions of Financial Records Keeping and Reporting Practices among Micro And Small Enterprises#x2019; a Case of Wollega Zonal Administration - Western Oromia Region (Global Journal of Management and Business Research, 2019)
Today, most of developing country economy is changed through MSE business operation were Ethiopia is a part. In this regard the financial record keeping and reporting practice of MSE has got much attention. This study aims to look at perception of financial record keeping and reporting practice of MSE in case of four Wollega zonal administrations. The target population of this study was 5,145MSEs found in the selected four towns that are engaged in different sectors. A simple random sampling technique was adopted. A sample of 194 was taken by using Slovin#x2019;s Sampling formula. The required data is collected from 178 sample (around 91%) respondents using self-administered five point-likert scale questionnaires. Data collected is processed by using SPSS version 16 software and STATA 10 and analyzed by using different descriptive statistics. Multinomial regression model was also adopted. The study reveals that, even though there is willingness of financial record and report makes to understand what is going on in their businesses, MSE have perceived that, they have not initiated by them-selves rather it is by the external push and they consider record keeping is a tedious activity. In regard with Knowledge, MSE owner and employees have no basic knowledge of bookkeeping and accounting
Keywords: record keeping; financial report; micro and small enterprises